Characterisation of Zika virus infection in primary human astrocytes - Stefanik, Michal; Pokorná, Petra; Bily, Tomas; Vancova, Marie; Eyer, Luděk; Palus, Martin; Salat, Jiri; Braconi, Carla Torres; Zanotto, Paolo M de A; Gould, Ernest A; Růžek, Daniel (BMC neuroscience, 2018)
BACKGROUND: The recent Zika virus (ZIKV) outbreak has linked ZIKV with microcephaly and other central nervous system pathologies in humans. Astrocytes are among the first cells to respond to ZIKV infection in the brain and are also targets for virus infection. In this study, we investigated the interaction between ZIKV and primary human brain cortical astrocytes (HBCA). RESULTS: HBCAs were highly sensitive to representatives of both Asian and African ZIKV lineages and produced high viral yields. The infection was associated with limited immune cytokine/chemokine response activation; the highest increase of expression, following infection, was seen in CXCL-10 (IP-10), interleukin-6, 8, 12, and CCL5 (RANTES). Ultrastructural changes in the ZIKV-infected HBCA were characterized by electron tomography (ET). ET reconstructions elucidated high-resolution 3D images of the proliferating and extensively rearranged endoplasmic reticulum (ER) containing viral particles and virus-induced vesicles, tightly juxtaposed to collapsed ER cisternae. CONCLUSIONS: The results confirm that human astrocytes are sensitive to ZIKV infection and could be a source of proinflammatory cytokines in the ZIKV-infected brain tissue.
Keywords: cytokiny; kultivované buňky; Zika Virus; Astrocytes; Brain; Cells, Cultured; virus zika; infekce virem zika; mozek; astrocyty; endoplazmatické retikulum; Zika Virus Infection; Cytokines; Humans; lidé; Endoplasmic Reticulum